Job Insecurity on Burnout in Kupang City Government Employees, East Nusa Tenggara - Ndun, Catherine Claudya; Wijaya, R. Pasifikus Ch.; Aipipidely, Diana (Journal of Health and Behavioral Science, 2023)
The Kupang City Government is expected to create a comfortableenvironment for employees to minimize burnout. This study aims to determine theeffect of job insecurity on burnout in Kupang City Government Employees. Theparticipants in this study were 359 employees who worked in 10 government officesof the City of Kupang, East Nusa Tenggara, who were selected using a randomcluster sampling technique. This study uses a quantitative approach with theMultidimensional Qualitative Job Insecurity Scale (MQJIS) (Cronbach’s alpha =0.764) to measure the independent variables and The Maslach Burnout Inventory(MBI) Scale (Cronbach’s alpha = 0.797) for the dependent variable. This study used asimple regression test with the help of the SPSS Statistics 25.0 application. Theresults showed that the value of R = 0.667 with p = 0.000 <0.01 and R² = 0.445. Thisshows a positive relationship between job insecurity and burnout, where jobinsecurity accounts for 44.5% of burnout. This means that job insecurity has a largeeffect on burnout. Hopefully, this research can provide information, thoughts, andinput to the Kupang City Government regarding job insecurity and burnoutexperienced by employees